Role of Botanical Herbs Used in Covid-19 Treatment and Cure - Chauhan , Kavita; Gupta, Amulya; Agrawal, Shruti (Plantae Scientia, 2021)
Corona 2019 (COVID-19) is a new infectious disease caused by acute respiratory syndrome corona virus 2 (SARS-CoV-2) which belongs to the family of corona viruses. The first case appeared in December 2019, and the disease has transformed into a pandemic. Physical disability control is one of the main parts that play a role in its disease and leads to adverse effects for COVID-19 patients. At present, people believe taking herbal treatment that can stop COVID-19. Medicinal plants can distribute as the therapeutic agents so it can help people to fight against the COVID-19 disease by boost their immunities. And such as, it can help to decrease the death rate that are linked with SARS-CoV-2 infections. So, in this analysis, we can make an effort to combine and talk about of different kind of traditional medicinal plants and their biological properties that can help to build-up our immune system and also play a biggest role in the fight against the viral infections including COVID-19. This document will help researchers and industry to recognize and assess in the making medicinal herb that can meet their needs in a variation of applications including herbal / ayurvedic antiviral products, anti-bacterial/antimicrobial design, immune-potentiator development, sanitization and sanitization programs.